STUDY ON TWO STATE ENERGY-SAVING VANE PUMP - ZHAI JianHua; LI YiFan; WEI XiaoHua (Jixie qiangdu)
In this paper,the design of a blade retractable vane pump was demonstrated. The combination of a vane pump with a plug-in type pilot-operated directional control valve can achieve the shift between the two states of oil supply and unloading of the vane pump. In addition,the damping effect of the directional valve makes it possible for the extension of the vane even in the high pressure portion. The axial clearance model was established to calculate the leakage power loss and the shear loss of the oil film. The relationship between the total power loss and the axial clearance was set up to obtain the optimal axial clearance.Furthermore,the condition of blade retraction under unloaded state was concluded and the temperature increase caused by oil film shear was calculated based on the theory of hot wedge oil film. Force exerted on the blade due to oil film expansion under the increased temperature was also verified. The conclusion of blade retraction condition during unloading of the vane pump enables the potential for future applications and further researches.